Non-coding RNAs in Regulating Tumor Angiogenesis - Song, Xin; Guo, Yanan; Song, Peng; Duan, Dongzhu; Guo, Wenjing (Frontiers in Cell and Developmental Biology, 2021)
Noncoding RNAs (ncRNAs) are RNAs that do not encode proteins, but perform biological functions in various physiological and pathological processes, including cancer formation, inflammation, and neurological diseases. Tumor blood vessels are a key target for cancer management. A number of factors regulate the angiogenesis of malignant tumors. NcRNAs participate in the regulation of tumor angiogenesis. Abnormal expression of ncRNAs act as tumor suppressors or oncogenes to affect the development of tumors. In this review we summarized the biological functions of ncRNAs, and discussed its regulatory mechanisms in tumor angiogenesis. This article will provide new insights for the research of ncRNAs in tumor angiogenesis.